City Prosperity Initiative Index: Using AHP Method to Recalculate the Weights of Dimensions and Sub- Dimensions in Reference to Tehran Metropolis - Arbab, Parsa (European Journal of Sustainable Development, 2017)
City Prosperity Initiative (CPI) as a comprehensive multidimensional index agreed globally, is a broad and flexible conceptual framework for measuring and monitoring the urbanization and urbanism as a consequence of this process. This initiative is a fundamental approach for defining an integrative and incremental vision and subsequently multi-sectorial and spatial analysis based direction for its fulfilment towards the sustainability path and sustainable urban development in different hierarchical levels and scales of global, national, regional, and local. The CPI is accompanied by a conceptual matrix, the Wheel of Urban Prosperity, in terms of six key components or dimensions associated with the city and urban settlement, including Productivity, Infrastructure Development, Quality of Life, Equity and Social Inclusion, Environmental Sustainability, and Urban Governance and Legislation. Each of these aspects includes 3 to 5 sub- dimensions defined and measured by a group of variables or indicators. Thus, the City Prosperity Initiative Index is essential basis to found and promote a new pattern or model of urbanization in the global scale which is adaptive to the contextual conditions and dynamics. Therefore, one of the most key issues in relation to the CPI Index is the weights of the dimensions and sub-dimensions in terms of the conceptualizations of a prosperous city based on the local priorities. Accordingly, this paper has been focused on the City Prosperity Initiative Index and subsequently recalculating the weights of its dimensions and sub-dimensions using Analytic Hierarchy Process (AHP) method according to the contextual situation of Tehran Metropolis in Iran. Keywords: City Prosperity Initiative (CPI) Index, Sustainability, Urban Prosperity, Analytic Hierarchy Process (AHP) Method, Tehran Metropolis